Corak Penafsiran Al-Qur'an Periode Klasik Hingga Modern - Danial Danial (Hikmah: Journal of Islamic Studies, 2019)
Al-Qur'an as a source of knowledge and life, therefore it is needed a method in exploring the treasure of knowledge which are contained inside it, not only the method needed. Since the vastness of interpretation study, so, many kinds of scientific approaches have been used to understand it. This writing is a part of research in order to explore many styles of interpretation since classical period to contemporary, which were compiled and formulated by the scholars, the writer sees the importance of detecting how far is that formulation can be used and developed in the al-Qur'an studies. Until now, interpreter scholars will continue to develop various fields of science in order to approach the Qur'an, until the virtues of al-Qur'an can be obtained and used as good as possible. These interpretation styles use the bi al-ra'yi interpretation form, which has always been a clash among the scholars in determining the position of these styles, some accept and some reject. It is also found in this article that every scholars has differences in concluding the number of interpretation styles from classical period until modern, those differences are because of the time and object that is being researched, at least, the writer finds some styles of interpretation, such as fikih interpretation style, sufi interpretation style, philosophy, madzhab interpretation style, language literature interpretation style, iImi interpretation style, ilhadi interpretation style, adabi Ijtima’i interpretation style, haraki interpretation style. Keywords: Style, Interpretation, Clasic, Modern Al-Qur’an sebagai sumber ilmu dan kehidupan, olehnya itu dibutuhkan metode dalam menggali khazanah keilmuan yang terkandung didalamnya, tidak hanya metode yang dibutuhkan. Karena betapa luasnya kajian penafsiran sehingga berbagai pendekatan ilmu digunakan untuk memahaminya. Tulisan ini merupakan bagian dari penelitian dalam rangka menggali berbagai corak-corak penafsiran sejak zaman klasik hingga kontemporer, yang disusun dan dirumuskan oleh para Ulama, penulis melihat pentingnya mendeteksi sejauhmana rumusan tersebut dapat digunakan dan dikembangkan dalam kajian al- Qur’an. Sampai saat ini ulama tafsir akan terus mengembangkan berbagai bidang keilmuan dalam rangka mendekati al-Qur’an, hingga mutiara-mutiara al-Qur’an dapat diperoleh dan digunakan sebaik mungkin. corak-corak penafsiran tersebut menggunakan bentuk penafsiran bi al-ra’yi, yang sejak dulu terjadi pertentangan ulama dalam menentukan kedudukan dari corak-corak tersebut, ada yang menerima dan ada pula yang menolak. Pada artikel ini juga ditemukan bahwa setiap ulama berbeda dalam menyimpulkan jumlah corak-corak tafsir dari klasik hingga modern, perbedaan tersebut disebabkan karena masa dan objek yang sedang diteliti, setidaknya penelis menemukan beberapa corak tafsir diantaranya, corak tafsir fikih, corak tafsir Sufi, Filsafat, corak tafsir mazhab, corak tafsir sastra bahasa, corak tafsir Ilmi, corak tafsir ilhadi, corak tafsir Adabi Ijtimā’i, corak tafsir akhlaqy, corak tafsir haraki. Keywords: Corak, Tafsir, Klasik, Modern